Multi-Dimensional Factor Correlation, Multiple Interbank Network Contagion, and Conditional VaR of Banks - Wang, Zhouwei; Zhao, Qicheng; Qiu, Lu (Frontiers in Physics, 2022)
The systemic risk of banks is a multi-dimensional factor correlation and multi-interbank contagion, forming a multi-dimensional multi-correlation (MDMC) contagion risk. After superposition, the multiplier effect magnifies the destructive power of a single impact. In this study, the weighted average method is used to integrate the four interbank contagion paths of jump-diffusion, interbank lending, stock price information, and common assets, establish the multi-level interbank contagion matrix, apply the quantile estimation of the spatial Dubin panel model, estimate the MDMC infectious bank conditional risk value, and decompose and identify the systemically important risk factors, systemically important banks, and systemically vulnerable banks. The following conclusions were drawn. First, the superposition contagion effect of MDMC networks is significant. Second, the systemic importance of default risk, interest rate risk, liquidity risk, and the GDP growth rate of the banking industry is high, followed by changes in stock market returns and investor sentiment. Third, the four major state-owned banks have an MDMC network contagion effect, which has the characteristics of systemic importance and vulnerability.